The Boost Team: transforming outreach for female veterans in rural communities - Cohen, Jenny Krause; Zamora-Rogoski, Kara; McLean, Caitlin; Jacob, Mariam; Stacker, Tara; Dancu, Caroline; Childers, Jennifer (Frontiers in Health Services, 2025)
IntroductionPrior studies show that rurality and sex act synergistically resulting in poor health outcomes for rural female Veterans in large part due to challenges utilizing timely and convenient health care services. We conducted a mixed-methods quality improvement evaluation of a novel outreach program within the Veterans Health Administration (VHA) that provides clinician-driven outreach to women Veterans served by rural VHA clinics. Our goal was to understand the impact the program has on rural female Veterans' access to and engagement in VHA care as well as the impact the program has on health system leaders and rural VHA clinic staff.Materials and methodsIn 2022, we developed a clinician-driven outreach program known as The Boost Team. The Boost nurse practitioner (NP) “cold called” female Veterans within a regional VA health care system and provided real-time clinical care and linkage to VHA services. Outreach calls were completed with 543 Veterans and metrics on call attempts and services rendered were tracked. Of Veterans who received the outreach, 58 completed a telephone survey using the Patient Empowerment Engagement Activation Survey (PEEAS), and 21 completed a semi-structured interview. Interviews focused on experiences with the NP, Boost's impact on access to and experience of VHA care, and suggestions for program improvement. Health system leaders (HSLs; n = 11) and rural VHA clinic staff (n = 5) completed interviews focused on barriers and facilitators to wider implementation of the Boost Program.FindingsThe most common needs addressed during outreach calls included new referrals to specialty care, completion of outstanding health care maintenance (e.g., age-appropriate cancer screening), coordination with primary and specialty care, assistance with medication management, and reviewing diagnostics (e.g., labs, imaging). PEEAS data demonstrated strong agreement across all categories (median = 5 or “strongly agree”). Veterans, HSLs, and clinic staff reported that Boost outreach increased trust in VHA among Veterans and provided necessary support for under-staffed clinics.ConclusionsClinician-driven outreach is a powerful tool to improve access to and engagement in care for rural female Veterans and provides necessary support to rural VHA clinics. Future efforts include expanding geographic range of Boost and better characterizing populations of veterans that most benefit from clinician-driven outreach.